The Canterbury Tales - Chaucer, Geoffrey; A Verse Translation With an Introduction and Notes by David Wright (Oxford New York Oxford University Press, 1998)
Provides a modern verse translation of the story of a group of pilgrims who pass the time during their journey by telling each other tales.
Include Bibliography, Table and Index
Keywords: England--Canterbury -- Christian pilgrims and pilgrimages -- Narrative poetry, English -- Children's plays, English